A Scientometric Analysis of Urban Economic Development: R Bibliometrix Biblioshiny Application - Nanang Rusliana; Ade Komaludin; Muhamad Ferdy Firmansyah (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2022)
This study aims to analyze the development of scientometric research from the theme of urban economic development. The analysis was carried out on 360 articles indexed by Dimension.ai. The method used is scientometric using R Bibliometrix Biblioshiny and VosViewer as processing tools. The results obtained are that this theme has begun to develop significantly in 2020 until now. Research in urban economic development is dominantly published by Chinese authors and affiliates in reputable journals. Research opportunities from urban economic development in emerging themes found the topics of city, innovation, metropolitan, planning, future, and change. This indicates that the potential research themes are in the city planning area which is “innovative”, “future-oriented” and able to “adapt the technology” in “the face of change”. Potential topics in urban economic development were found to have changed from 1964-2013 to 2014-2020 which focused on urban, data, local, contemporary, design and cities. These results can be used as input in compiling research on the theme of urban economic development research and to help researchers find novelty and sustainable impact contributions.